(untitled) - World Bank (WB) (Washington, DC, 2007)
The Inspection Panel is an independent accountability mechanism of the World Bank. It was established in September 1993 by the World Bank Board of Directors, and started operations on August 1, 1994. The Panel provides a forum for people who believe that they may be adversely affected by Bank-financed operations to bring their concerns to the highest decision-making levels of the World Bank. The Panel determines whether the Bank is complying with its own policies and procedures, which are designed to ensure that Bank-financed operations provide social and environmental benefits and avoid harm to people and the environment. The Inspection Panel was the first body to promote accountability among international financial institutions through this community-led, or “bottom-up”, approach which is complementary to the “top-down” forms of accountability, such as evaluation initiated by the World Bank itself.
Keywords: Economic development projects,Economic development projects,Dự án phát triển kinh tế,Dự án phát triển kinh tế; Evaluation,Đánh giá; Development countries,Nước đang phát triển